2017
DOI: 10.1002/acm2.12057
|View full text |Cite
|
Sign up to set email alerts
|

Linac‐based stereotactic radiosurgery (SRS) in the treatment of refractory trigeminal neuralgia: Detailed description of SRS procedure and reported clinical outcomes

Abstract: Purpose/ObjectivesTo present our linac‐based SRS procedural technique for medically and/or surgically refractory trigeminal neuralgia (TN) treatment and simultaneously report our clinical outcomes.Materials and MethodsTwenty‐seven refractory TN patients who were treated with a single fraction of 80 Gy to TN. Treatment delivery was performed with a 4 mm cone size using 7‐arc arrangement with differential‐weighting for Novalis‐TX with six MV‐SRS (1000 MU/min) beam and minimized dose to the brainstem. Before each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Pokhrel et al reported a detailed study for the treatment of TN with clinical outcomes for Novalis Tx with 27 patients and found that the average MU were 19,440 ± 611, average BOT was 19.4 ± 0.6 minutes and the maximum brainstem dose 15.9 Gy for an 80 Gy prescription. In our study, we were also able to achieve the same for Novalis Tx with average MU 19,869 ± 543, average BOT 19.72 ± 1.1 minutes and a maximum brainstem dose of 14.8 Gy [23]. There is only one study reported using Truebeam with FFF beams for the treatment of TN [24].…”
Section: Discussionsupporting
confidence: 65%
“…Pokhrel et al reported a detailed study for the treatment of TN with clinical outcomes for Novalis Tx with 27 patients and found that the average MU were 19,440 ± 611, average BOT was 19.4 ± 0.6 minutes and the maximum brainstem dose 15.9 Gy for an 80 Gy prescription. In our study, we were also able to achieve the same for Novalis Tx with average MU 19,869 ± 543, average BOT 19.72 ± 1.1 minutes and a maximum brainstem dose of 14.8 Gy [23]. There is only one study reported using Truebeam with FFF beams for the treatment of TN [24].…”
Section: Discussionsupporting
confidence: 65%
“…The reported patient numbers in series using LINAC SRS for the treatment of TN are comparatively fewer [ 19 24 , 28 , 35 38 ], consequentially fewer numbers of patients can be reviewed in total, but there are also some smaller prospective LINAC studies (for review see [ 25 ]). Synoptically, the reported success rates are very similar to the published rates of GK therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 , 7 , 8 , 9 Although these methods have supplanted cones in the treatment of metastases and larger benign targets such as arteriovenous malformations and acoustic schwannomas, cones remain the standard for functional targets, in particular trigeminal neuralgia. 10 , 11 , 12 , 13 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%